Protective effects of coffee consumption following liver transplantation for hepatocellular carcinoma in cirrhosis. Issue 6 (27th February 2019) - Wiltberger, Georg; Wu, Yan; Lange, Undine; Hau, Hans‐Michael; Tapper, Elliot; Krenzien, Felix; Atanasov, Georgi; Benzing, Christian; Feldbrügge, Linda; Csizmadia, Eva; Broschewitz, Johannes; Bartels, Michael; et al.
Summary: Background: Increasing evidence suggests that coffee consumption might protect against hepatocellular carcinoma (HCC) and liver cirrhosis‐associated death risk. Caffeine is a natural antagonist to extracellular adenosine and exhibits experimental tumoricidal activity. Aim: To evaluate if coffee consumption has beneficial effects on HCC recurrence after orthotopic liver transplantation (OLT). Methods: Coffee consumption of patients before and after OLT for HCC was assessed and correlated with HCC recurrence. HepG2 cells were analysed for proliferation and metastasis potential after treatment with adenosine, in the presence or absence of adenosine receptor antagonists. Expression of adenosine receptors was determined, and known adenosine‐mediated cancer pathways inclusive of MAPK and NF‐kappa B were tested. Results: Ninety patients underwent OLT for HCC. Sixteen (17.8%) patients experienced HCC recurrence after median time of 11.5 months (range 1‐40.5). For overall survival postoperative coffee intake emerged as major factor of hazard reduction in a multivariate analysis (HR = 0.2936, 95% CI = 0.12‐0.71, P = 0.006). Those with such postoperative coffee intake (≥3 cups per day) had a longer overall survival than those who consumed less or no coffee: M = 11.0 years, SD = 0.52 years vs. M = 7.48 years, SD = 0.76 years = 4.7, P = 0.029). Conclusions: Coffee consumption is associated with a decreased risk of HCC recurrence and provides for increased survival following OLT. We suggest that these results might be, at least in part, associated with the antagonist activity of caffeine on adenosine‐A2AR mediated growth‐promoting effects on HCC cells.